Comparison of Plyometric Training With Two Different Jumping Techniques on Achilles Tendon Properties and Jump Performances - Laurent, Cédric; Baudry, Stéphane; Duchateau, Jacques (Journal of strength and conditioning research, 2020)
Laurent, C, Baudry, S, and Duchateau, J. Comparison of plyometric training with two different jumping techniques on Achilles tendon properties and jump performances. J Strength Cond Res 34(6): 1503-1510, 2020-This study compared the influence of 10 weeks of plyometric training with 2 different jumping techniques on Achilles tendon properties and the height achieved in drop jumps (from 20, 40, and 60 cm) and countermovement jumps (CMJ). Subjects were allocated to 2 training groups (n = 11 in each group) and 1 control group (CON, n = 10). One training group kept the knees extended (KE) during ground contact, whereas the other training group flexed the knees to ∼80-90° (KF). Achilles tendon stiffness was assessed with ultrasonography, and jump performance was derived from force platform recording. Training increased jump height (p < 0.01) in both groups. The increase for the 20-cm drop jump was greater (p < 0.05) for the KE group (11.3%) thanfor the KF group (6.3%), with no statistical difference between groups for the 40- and 60-cm drop jumps. Contact time during the 20-cm drop jump decreased (∼8%; p < 0.01) after training, with no difference between the training groups. The increase in CMJ height was greater (p = 0.05) for the KF group (17.5%) than for the KE group (11.8%). Achilles tendon stiffness increased (32%; p < 0.001) for the KE group but not for the KF group (11%; p = 0.28). There was a positive association (p < 0.001) between the changes in tendon stiffness and jump height for 20-cm drop jump in both KE group (r = 0.49) and KF group (r = 0.62). None of these parameters changed in CON group. In conclusion, the extent of increase in jump height (20-cm drop jump and CMJ) and in Achilles tendon stiffness after training differed between the 2 jumping techniques.